Analysis and Modelling of the Measurable, Electrical HF-Quantities of an IPMSM and their Dependencies - Hittinger, Christoph; Graus, Johannes; Hahn, Ingo; Wagner, Johannes (Electrical Machines and Systems (ICEMS), 2016 19th International Conference on, 2016)

Analytic power factor calculation for vernier machines with concentrated windings - Thyroff, Dominik; Hittinger, Christoph; Hahn, Ingo (2017 IEEE International Electric Machines and Drives Conference (IEMDC), 2017)
It is well-known that the power factor of Vernier machines is small compared to permanent magnet machines. However, the power factor equations already derived show a huge deviation to the finite-element analysis (FEA) when used for Vernier machines with concentrated windings. Therefore, this paper develops an analytic model to calculate the power factor of Vernier machines with concentrated windings and different numbers of flux modulating poles (FMPs) and stator slots. The established model bases on the winding function theory in combination with a magnetic equivalent circuit. Consequently, equations for the q-inductance and for the no-load back-EMF of the machine are derived, thus allowing the calculation of the power factor. Thereby, the model considers stator leakage effects, as they are crucial for a good power factor estimation. Comparing the results of the Vernier machine to those of a pm machine explains the decreased power factor of Vernier machines. In addition, a FEA confirms the results of the derived model.
Keywords: equivalent circuits; finite element analysis; machine windings; magnetic circuits; permanent magnet machines; power factor measurement; stators; FEA; Vernier machines; analytic model; analytic power factor calculation; back-EMF; concentrated windings; finite-element analysis; flux modulating poles; magnetic equivalent circuit; permanent magnet machines; power factor estimation; stator leakage effects; stator slots; winding function theory; Analytical models; Integrated circuit modeling; Mathematical model; Reactive power; Stator windings; Windings; Vernier machine; analytic model; concentrated windings; leakage; magnetic equivalent circuit; power factor

Comparison of the Power Factor of SMPM and SM Vernier Outer Runner Machines for Traction Applications - Thyroff, Dominik; Hittinger, Christoph; Hahn, Ingo (2018 IEEE International Magnetics Conference (INTERMAG), 2018)
Low voltage traction applications demand high torques at low speeds and at a small design space. In order to achieve high torque densities, manufacturers often combine high-speed machines with mechanical gearboxes. In the past decade, flux modulation machines came up, offering low speeds and high torque densities by utilizing the magnetic gearing effect. The idea is to remove the mechanical gear and get a compact direct drive solution. Now, the Vernier machines are a subgroup of the flux modulation machines. However, literature reports very poor power factors for Vernier machines in comparison to PM machines as the main drawback. Nevertheless, the presented studies always assume a fixed speed and only one single current operating point. This is correct for fixed speed applications, e.g. pumps and blowers, but it is not correct for traction applications, because the machine cycles dynamically through the torque-speed curve. Therefore, this paper first investigates the machine design requirements considering the machine control strategies and the needs of traction applications. Furthermore, a method to check if the design fulfills the given requirements by calculating only a single operating point is presented. In addition, the emerging differences between Vernier and PM machines are explained using analytic results. Furthermore, the paper presents a power factor comparison of torque optimized Vernier and PM machines while considering iron losses. Thereby, the comparison covers the whole torque-speed range, including the field weakening are
Keywords: finite element analysis; gears; machine control; magnetic flux; permanent magnet machines; power factor; rotors; torque; traction; machine cycles; torque-speed curve; machine design requirements; machine control strategies; single operating point; PM machines; power factor comparison; torque optimized Vernier; torque-speed range; SM Vernier outer runner machines; low voltage traction applications; high torques; low speeds; design space; high torque densities; high-speed machines; mechanical gearboxes; flux modulation machines; magnetic gearing effect; mechanical gear; compact direct drive solution; fixed speed; single current operating point; Torque; Reactive power; Magnetic flux; Gears; Trajectory; Couplings; Modulation; Vernier machine; power factor; control strategy; performance comparison

Examining the unstable behaviour of a phenomenological three dimensional, dipole-based hysteresis model - Wagner, Johannes; Hittinger, Christoph; Hahn, Ingo (20th International Conference on Electrical Machines and Systems, ICEMS 2017, 2017)
Keywords: Dipole-Collective; Hysteresis Modell; Field Computation; Magnetic Materials

Improved Sensorless Position Estimation of an IPMSM by Weighted Combination of Resistance-and Inductance-Based Saliency Tracking - Hittinger, Christoph; Hahn, Ingo (2018 21st International Conference on Electrical Machines and Systems (ICEMS), 2018)
Keywords: Rotors; Inductance; Resistance; Estimation error; Windings; Saturation magnetization; sensorless control; single-tooth winding; short-circuited rotor winding

Influence of Elementary Model Parameter Variations on Simulated Ferromagnetic Hysteresis Using a Ring-Shaped 3D Dipole Collective - Hittinger, Christoph; Wagner, Johannes; Hahn, Ingo (Electrical Machines and Systems (ICEMS), 2017 20th International Conference on, 2017)

Investigations on the Concept of Short-Circuited Rotor Windings for the Improvement of the Self-Sensing Capability of Electrical Machines - Hittinger, Christoph; Hahn, Ingo (2019 26TH INTERNATIONAL WORKSHOP ON ELECTRIC DRIVES: IMPROVEMENT IN EFFICIENCY OF ELECTRIC DRIVES (IWED) PROCEEDINGS, 2019)
CRIS-Team WoS Importer:2019-06-18

Modeling of an IPMSM with Short-Circuited Rotor Winding for Sensorless Position Estimation by FEA Using the Frozen Permeability Method - Hittinger, Christoph; Hahn, Ingo (Industrial Electronics Society , IECON 2017 - 43rd Annual Conference of the IEEE, 2017)

Modelling and Examination of the Influence of a Short-Circuited Rotor Winding for Saliency Tracking of a Machine with a Three-Phase Single-Tooth Winding - Hittinger, Christoph; Thyroff, Dominik; Hahn, Ingo (Electric Machines and Drives Conference (IEMDC), 2017 IEEE International, 2017)

Phenomenological Modelling of Ferromagnetic Hysteresis using three Dimensional Dipole Collectives - Wagner, Johannes; Hahn, Ingo; Hittinger, Christoph (ICEM 2016, 2016)
Knowing the magnetic properties of electrical steel is very important to build highly efficient electrical machines. Many approaches, which are either of mathematical, physical or phenomenological kind, were developed in the past in order to predict the phenomenon of hysteresis in case of unmeasured conditions. In this paper, a phenomenological 3D hysteresis model using magnetic dipoles, which are mechanically supported on a 3-dimensional grid, is presented. The different interactions between these dipoles are based on the equations of micromagnetism. Instead of minimizing the free energy in the system by mathematical optimization methods, each elementary dipole is able to rotate into an individual energetically favourable positon due to its mechanical mounting. In the following sections the model, its parameters and the identification process are presented. Afterwards, the results of the parameter identification process for a measured hysteresis are shown. Furthermore the predictive abilities of the model in case of unmeasured conditions are discussed.
Keywords: Dipole-Collective; Micromagnetism; Hysteresis; Hysteresis Modell; Electrical Steel; Ferromagnetism; Field Computation; Magnetic Materials

Resistance- and Inductance-Based Self-Sensing Control using Short-Circuited Windings on the Rotor of a SPMSM - Hittinger, Christoph; Hahn, Ingo (45th Annual Conference of the IEEE Industrial Electronics Society (IECON), 2019)
CRIS-Team WoS Importer:2020-05-15

Short-Circuited Rotor Windings for Improving the Electromagnetic Saliency for Inductance- and Resistance-Based Self-Sensing Control - Hittinger, Christoph; Hahn, Ingo (2019 IEEE 28th International Symposium on Industrial Electronics (ISIE), 2019)
Keywords: self-sensing control; resistance-based; inductance-based; short-circuited rotor windings; SPMSM